Outcomes of Severe Sepsis and Septic Shock Patients on Chronic Antiplatelet Treatment: A Historical Cohort Study - Juan C. Valerio-Rojas; Insara J. Jaffer; Daryl J. Kor; Ognjen Gajic; Rodrigo Cartin-Ceba (Critical Care Research and Practice)
Background. Sepsis is characterized by dysfunctional activation of platelets, and antiplatelet therapy could improve the outcomes of septic patients. Methods. We performed a retrospective cohort study of severe sepsis or septic shock adult patients. Outcomes of patients on antiplatelet therapy were compared to those that were not taking antiplatelet therapy by univariate analysis followed by a propensity score analysis based on the probability of receiving antiplatelet therapy. Results. Of 651 patients included in the study 272 (42.8%) were on antiplatelet therapy before the development of severe sepsis or septic shock. After adjusting for important confounding variables antiplatelet therapy was not associated with a decreased risk of hospital mortality (odds ratio 0.73, 95% confidence interval 0.46–1.16). Antiplatelet therapy was associated with a decreased incidence of acute respiratory distress syndrome/acute lung injury (odds ratio 0.50, 95% confidence interval 0.35–0.71) and reduced need of mechanical ventilation (odds ratio 0.62, 95% confidence interval 0.45–87). Incidence of acute kidney injury was similar between both groups (odds ratio 1.08, 95% confidence interval 0.73–1.59). Conclusions. The use of antiplatelet therapy before the diagnosis of severe sepsis or septic shock was not associated with decreased hospital mortality. Antiplatelet therapy was associated with a decreased incidence of acute lung injury/acute respiratory distress syndrome.